Bruton’s tyrosine kinase inhibition limits endotoxic shock by suppressing IL-6 production by marginal zone B cells in mice - Kawata, Kazuhiko; Hatano, Shinya; Baba, Akemi; Imabayashi, Keisuke; Baba, Yoshihiro (Frontiers in Immunology, 2024)
Sepsis is a systemic inflammatory response to a severe, life-threatening infection with organ dysfunction. Although there is no effective treatment for this fatal illness, a deeper understanding of the pathophysiological basis of sepsis and its underlying mechanisms could lead to the development of new treatment approaches. Here, we demonstrate that the selective Bruton's tyrosine kinase (Btk) inhibitor acalabrutinib augments survival rates in a lipopolysaccharide (LPS)-induced septic model. Our in vitro and in vivo findings both indicate that acalabrutinib reduces IL-6 production specifically in marginal zone B (MZ B) cells rather than in macrophages. Furthermore, Btk-deficient MZ B cells exhibited suppressed LPS-induced IL-6 production in vitro. Nuclear factor-kappa B (NF-kB) signaling, which is the downstream signaling cascade of Toll-like receptor 4 (TLR4), was also severely attenuated in Btk-deficient MZ B cells. These findings suggest that Btk blockade may prevent sepsis by inhibiting IL-6 production in MZ B cells. In addition, although Btk inhibition may adversely affect B cell maturation and humoral immunity, antibody responses were not impaired when acalabrutinib was administered for a short period after immunization with T-cell-independent (TI) and T-cell-dependent (TD) antigens. In contrast, long-term administration of acalabrutinib slightly impaired humoral immunity. Therefore, these findings suggest that Btk inhibitors may be a potential option for alleviating endotoxic shock without compromising humoral immunity and emphasize the importance of maintaining a delicate balance between immunomodulation and inflammation suppression.